A study on different types of seersucker fabric design by industrial scale production line - UZUN, MUHAMMET (My University, 2023)
With the growing perception of sustainability and vintage fashion trend, the textile industry is taking steps toward change and innovation with the benefit of recent technological development. Using traditional fabrics to modernize from the past to today’s technology is one of the most popular research and design topics. Fashion shows real proof that history repeats itself over and over again. Along with the modern developments increasing variety of fibers also helps to develop innovative product possibilities. Seersucker is not a common type of fabric. Seersucker actually refers to a style/pattern/texture that produces a puckering effect on the surface of the fabric with the textures smooth and coarse. In this study, first, a brief historical background of the seersucker fabrics is explained. The most used seersucker fabric types are determined to design and produce during this study. The selected patterns of seersucker fabrics with different fiber combinations were produced according to the common strip model, and their technical properties were tested and analyzed. 5 different types of fabrics are tested in terms of their structural properties, color fastness to water, color fastness to perspiration, etc.
Keywords: Seersucker Woven Fabrics; Fabric Mechanical Properties; Structural Design; Slow-Fashion; Sustainability